Evaluation of Heat Shock Proteins 70 (HSP70) and some Risk Factors in Sera of Rheumatoid Arthritis Patients in Thi-Qar Province - Al-Salih, Mutasim W M; Selman, Ali Naeem (Al-Nahrain Journal of Science, 2018)
Heat shock proteins (HSPs)were synthesized under different kinds of stress conditions and act as molecular chaperones for protein molecules. These proteins were first found in cells that were exposed to high temperature, they are called "heat shock protein. Several risk factors are involved in the pathogenesis of autoimmune rheumatic diseases, including genetic factors, smoking, chronic infections, sex hormones, stress and HSP 70. In this present study the role of heat shock protein 70 was investigated in pathogenesis and immune response in rheumatoid arthritis (RA). This study was conducted onfifty samples of rheumatoid arthritis patients. In addition twenty samples of superficially healthy volunteers. All these samples were used for determining the concentration of HSP70. The results of study demonstrate the existence of high significant difference (P≤0.001), between patients and control group when the concentration of HSP70 was measured for all samples. This study also demonstrates slight statistical differences (P≤0.05), among studied groups when taken into consideration the gender, age groups and characteristics of smoking. It is concluded that the concentration of HSP70 is increasing at the beginning of the disease and it is higher in RA patients compared with control, also it is higher in female than in male groups.